2021
DOI: 10.3389/fchem.2021.707387
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Mass Spectrometry-Based Glycomic and Glycoproteomic Studies of Pancreatic Diseases

Abstract: Modification of proteins by glycans plays a crucial role in mediating biological functions in both healthy and diseased states. Mass spectrometry (MS) has emerged as the most powerful tool for glycomic and glycoproteomic analyses advancing knowledge of many diseases. Such diseases include those of the pancreas which affect millions of people each year. In this review, recent advances in pancreatic disease research facilitated by MS-based glycomic and glycoproteomic studies will be examined with a focus on diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 155 publications
0
8
0
Order By: Relevance
“…These results emphasize the need for further studies evaluating Cf-MSLN in a larger cohort of patients, and including sera from other types of cancers in order to evaluate its specificity for PaC. Altogether, they show the importance of focusing on specific protein glycoforms altered in cancer, as well as exploring new glycoproteomic strategies [ 86 , 87 ] to high-throughput the analysis of Cf-MSLN and validate it as a PaC biomarker.…”
Section: Discussionmentioning
confidence: 75%
“…These results emphasize the need for further studies evaluating Cf-MSLN in a larger cohort of patients, and including sera from other types of cancers in order to evaluate its specificity for PaC. Altogether, they show the importance of focusing on specific protein glycoforms altered in cancer, as well as exploring new glycoproteomic strategies [ 86 , 87 ] to high-throughput the analysis of Cf-MSLN and validate it as a PaC biomarker.…”
Section: Discussionmentioning
confidence: 75%
“…Analysis of glycan structure requires the release of glycans. N -glycans are released from glycopeptides by peptide- N -glycosidase F (PNGase F) digestion ( 61 ). O -glycans have many core structures, and no general release enzymes are used; however, there are corresponding enzymes for specific core structures.…”
Section: Recent Advances In Glycomics-based Biomarker Discoverymentioning
confidence: 99%
“…O -glycans have many core structures, and no general release enzymes are used; however, there are corresponding enzymes for specific core structures. Alternatively, any O -glycans can be released through the chemical process of β-elimination, with the potential for undesirable side effects ( 61 ). In recent years, bottom-up MS has been widely used to study glycosylation changes in tumorigenesis and development at different specificity levels including global, cell-specific, and local-specific.…”
Section: Recent Advances In Glycomics-based Biomarker Discoverymentioning
confidence: 99%
“…One study identified the modulated pathways of PCSCs via iTRAQ-based proteomic analysis, revealing that PCSCs changed proteomic and metabolite profiling compared to Panc1 parental cells. FAs and mevalonate play pivotal roles in the survival of PCSCs ( 42 ). Another study used LC-MS/MS to examine the protein modulation and lipid modulations in four PCSCs ( 43 ).…”
Section: Hinting On the Pathogenesis Of Pc By Msmentioning
confidence: 99%